2016
DOI: 10.1513/annalsats.201609-680aw
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Target of Rapamycin: A Target for (Lung) Diseases and Aging

Abstract: The mammalian target of rapamycin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Collectively, these data provide new insights into the protective role of MTOR in COPD pathogenesis through the suppression of cell death and inflammation in the lung. Moreover, the current study also provides possible mechanistic explanations for the adverse pulmonary effects of MTOR inhibitors in clinical use (20,21).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Collectively, these data provide new insights into the protective role of MTOR in COPD pathogenesis through the suppression of cell death and inflammation in the lung. Moreover, the current study also provides possible mechanistic explanations for the adverse pulmonary effects of MTOR inhibitors in clinical use (20,21).…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, despite the functions of autophagy in regulation of CS-induced apoptosis, cilia loss, and mucus production, the role and mechanisms of autophagy in CS-induced chronic airway inflammation are not well investigated. Interestingly, patients with breast cancer, renal cell carcinoma or other diseases, treated with MOTR inhibitors tend to develop dyspnea, cough or interstitial lung disease (20,21), but the underlying mechanisms remain unclear.…”
mentioning
confidence: 99%
“…By examining the process of apoptosis and trans-differentiation, we provide insights into the molecular basis of tissue remodeling in chronic lung disease. Importantly, the roles of autophagy and the use of Rapamycin have been considered in the context of COPD and Asthma, were tested in various models, but with variable effects (Kennedy and Pennypacker, 2016;Lam et al, 2013;Mitani et al, 2016;Mushaben et al, 2011;Wang et al, 2018). Cell type-specific effects of Rapamycin in the airways were discussed, but without reaching a consensus.…”
Section: Discussionmentioning
confidence: 99%
“… 29 As pharmacologic inhibitors of mTOR, such as everolimus and sirolimus, can directly inhibit T-lymphocyte proliferation, there is ample evidence that mTOR inhibitors are effective for the treatment of pulmonary and renal LAM. 30 34 Li et al reported that IGFBP2 could bind insulin, IGF1, and IGF2 in the circulation to modulate cell survival, migration, and invasion of neoplasms. Targeting IGFBP2 may serve as a potential therapeutic strategy for women with LAM and other female gender-specific neoplasms.…”
Section: Discussionmentioning
confidence: 99%